Analysis of Students' Knowledge Sources (Resource Theory) in Rolling Motion Context and Its Implementation in Physics Learning - Herlina Mulyastuti; M Amien Rais (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
Resource theory is a cognitive theory that can explain students' difficulties in understanding physics concepts and be a basis for developing meaningful physics learning. However, studies on resource theory have been used more to analyze learning difficulties and identify student resources only. Through this research, we developed an inquiry-based learning model by considering students' initial resources, implement it, and see resource changes after learning. This article describes changes in students' resources regarding the phenomenon of rolling motion from before to after learning. The research subjects were 32 students of class XI MIPA at Senior High School. Student resources were identified based on student's answers to the pretest and posttest using a reasoned multiple-choice instrument, then analyzed qualitatively using a constant comparison technique. Several resources were revealed based on students' reasons for their answers during the pretest, all classified as phenomenological primitives. Based on students' reasons for their answers during the posttest, it can be concluded that learning can help most students organize scientific resources and identify the context in which they can be used.